CURRENT PROBLEMS OF LABOR REGULATION: THEORETICAL AND LEGAL ASPECT - Stadnichenko, Serhiy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to consider the peculiarities of employment in modern conditions, to analyze the main legal acts regulating legal relations in the field of labor, to single out proposals for improving the employment process. Research methods: general scientific and special methods were used during scientific research. In particular, the logical-semantic method, the comparative-legal method. With the help of these methods, a set of socio-legal relations related to a person obtaining a job, taking into account his abilities and capabilities, which will satisfy his needs in ensuring his existence and the existence of his family, as well as in continuous development as an individual, in science, is outlined and in practice the application of the concept of "employment", which is currently the object of research in many areas of scientific knowledge. Results: it is argued that, taking into account the current conditions in which Ukraine is, legal relations in the field of labor require additional normative and legal regulation. Discussion: аccording to Art. 43 of the Constitution of Ukraine, everyone has the right to work, which includes the opportunity to earn a living by work that he freely chooses or freely agrees to. The state undertakes to create conditions for the full exercise of the right to work by citizens, guarantees equal opportunities in choosing a profession and type of work, and also implements programs of professional and technical education, training and retraining of personnel in accordance with public needs. However, in today’s conditions, Ukraine is under the legal regime of martial law. On this path, the state identified priority areas, namely: protection of sovereignty and territorial integrity. But it has resorted to violating the legal rights of citizens, and the sphere of labor is no exception. Therefore, this scientific work touches on the issue of inefficiency in the regulation of labor relations in the conditions of the legal regime of martial law, the main normative legal acts that regulate this sphere of legal relations are analyzed.